Fiqh Minoritas; Penelusuran Basis Konsep Minoritas dalam Al-Qur’an dan Operasionalisasinya - Dimyati, Ahmad (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
This article aims to offer minority fiqh as a solution to the implementation of Islamic law (fiqh) in various regions, especially for Muslims who live as a minority. There are two important findings that the author concludes in this article, first, the use of the terminology minority and majority is used in the Qur'an in very diverse contexts. Interestingly, the term majority is used in the context of negative meanings, such as polytheists, infidels, negligent, and opposing Islamic teachings. While the use of the terminology minority has a positive connotation, referring to meanings such as believers, survivors, and so on. In line with the differences in context, classical fiqh has recognized minorities in the concepts of dzimmah, mu'ahadah, and musta'man. Second, the development of minority fiqh is carried out by applying collective ijtihad (jama'i), applying al-Qawa'id al-Fiqhiyah (legal maxim), understanding the historical context, applying the principle of facilitation (muyassar), oriented towards universal fiqh, and protecting the identity of individual Muslims while connecting it to the collective identity of Muslims.